International Participation of Subnational Actors: Contributions to Study University - Calvento, Mariana (2012)
International participation of subnational actors is a contemporary issue that emerged mainly as a result of globalizer processes, national transformations and redefinition of decentralization processes experienced in the past three decades. These processes have led to the external participation of different actors, such as companies, cities, universities, civil society organizations, subnational government institutions and even individuals. However, the process of international involvement of these actors in the same national and international scene has been diverse. Within the variety of actors above mentioned, it has become particularly active the international involvement of universities. This paper presents a framework of analysis to explain the reasons why certain universities have achieved a certain level of internationalization. It seeks to link the development of the international dimension to the capabilities of the institution; specifically this framework considers as relevant the notion of “state capacity”.